Towards a review of the legal language in court sentences - Mendes Batista, Gisele (2022)
Based on the assumption that law has as its foundation of validation the people themselves, and aligned with the plain language movement, this paper initially discusses the role of technical language in the scope of the community of legal practices and the effects of its extrapolation to civil society. It also discusses the social implications of the exacerbation of the use of area jargon in legal language, as well as analyzes mechanisms that monopolize and democratize this access to legal content. Finally, an experimental study is carried out to measure civil society's perception of legal language, identifying points that may contribute to its democratization. The investigation concludes that the simplification of the language, without de-characterizing the legal technique, contributes to the understanding of legal content, which signals the importance of training actions in the area of simple language aimed at the law.